Feeding on rapid cold hardening Ambrosia artemisiifolia enhances cold tolerance of Ophraella communa - Tian, Zhenqi; Ma, Chao; Zhang, Yan; Chen, Hongsong; Gao, Xuyuan; Guo, Jianying; Zhou, Zhongshi (Frontiers in Plant Science, 2023)
Low temperatures greatly influence newly introduced species, and increased cold tolerance can facilitate their establishment in new environments. The invasive alien species Ambrosia artemisiifolia is distributed at high latitudes and altitudes, where it suffers more from cold stress than it would at low latitudes or altitudes. Whether cold stress influences the accumulation of cryoprotectants and cold tolerance in A. artemisiifolia, and further influences the cold tolerance of its biological control agent, Ophraella communa, through feeding remain unknown. We investigated the levels of cryoprotectants and metabolic changes in A. artemisiifolia. We found that the level of total sugar, trehalose, proline, and other cold responsible metabolites increased in A. artemisiifolia after rapid cold-hardening (RCH) treatment, when compared to normal plants. These indicated that RCH treatment could improve the cold-hardiness of A. artemisiifolia. We then investigated the levels of cryoprotectants and metabolic changes in O. communa. We found that O. communa fed on RCH-treated A. artemisiifolia had higher levels of total sugar, trehalose, proline, glycerol, lipid, lower water content, lower super-cooling point, and increased cold tolerance compared to O. communa fed on normal A. artemisiifolia. This suggested that O. communa fed on cold-hardened A. artemisiifolia could increase its cold tolerance. Results showed a trophic transmission in insect cold tolerance. Our study enriches the theoretical basis for the co-evolution of cold tolerance in invasive and herbivorous insects.